1994
DOI: 10.1038/bjc.1994.462
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein and glutathione S-transferase pi in childhood acute lymphoblastic leukaemia

Abstract: Summary Blast cells obtained from 104 children with untreated acute lymphoblastic leukaemia were analysed for the expression of P-glycoprotein (P-170) and glutathione S-transferase (GST-it) using immunohistochemistry. Expression of P-170 was detected in 36 of 104 patients (35%) and increased GST-i was seen in 52 patients (50%). Coexpression of both resistance proteins was observed in 22 leukaemias (21 %), whereas no evidence of the resistance markers was found in 38 cases (37%). In patients with P-170-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…Although the clinical significance of P-gp has been to necrotic death. Using the Kolmogoroff-Smirnoff test we described in some reports, 15,16 others did not 17,18 suggesting found that only unaided spontaneous apoptosis after 24 h the existence of non-P-gp-mediated mechanisms of resistance. incubation in vitro was significantly different (D = 0.7, Despite the correlation of induction of apoptosis by DNR ␣ = 0.05).…”
Section: Figurementioning
confidence: 93%
“…Although the clinical significance of P-gp has been to necrotic death. Using the Kolmogoroff-Smirnoff test we described in some reports, 15,16 others did not 17,18 suggesting found that only unaided spontaneous apoptosis after 24 h the existence of non-P-gp-mediated mechanisms of resistance. incubation in vitro was significantly different (D = 0.7, Despite the correlation of induction of apoptosis by DNR ␣ = 0.05).…”
Section: Figurementioning
confidence: 93%
“…[9][10][11][12] Some show that its expression might be related to poor survival or risk of relapse, whereas others show no prognostic significance. [13][14][15][16][17][18][19][20] Studies using cyclosporins to modulate MDR [21][22][23][24][25] have been performed in children with AML or retinoblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…37 Inconsistent data about the contribution of P-gp to drug resistance and treatment outcome have also been reported in childhood acute leukemia. 23,[38][39][40][41][42] We recently showed that expression of P-gp and MRP did not correlate with the intracellular DNR concentration and in vitro resistance to DNR in a large series of childhood ALL samples. 17,43 In contrast, the expression of LRP inversely correlated with the in vitro cytotoxicity and intracellular concentration of DNR.…”
Section: Discussionmentioning
confidence: 99%